2021
DOI: 10.1186/s12870-021-03068-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics identifies key defense mechanisms in rice resistant to both leaf-feeding and phloem feeding herbivores

Abstract: Background Outbreaks of insect pests in paddy fields cause heavy losses in global rice yield annually, a threat projected to be aggravated by ongoing climate warming. Although significant progress has been made in the screening and cloning of insect resistance genes in rice germplasm and their introgression into modern cultivars, improved rice resistance is only effective against either chewing or phloem-feeding insects. Results In this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 86 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…A recent study showed that a rice variety from Taiwan, Qingliu, displays a rarely observed dual resistance to the leaffolder (chewing insect) and the BPH. Although the responses of Qingliu to both insect pests appear vastly dissimilar, the phenylpropanoid pathway could be a convergent upstream pathway [65]. This study showed that the phenylpropanoid pathway is valuable for generating broad-spectrum resistance in rice cultivars.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study showed that a rice variety from Taiwan, Qingliu, displays a rarely observed dual resistance to the leaffolder (chewing insect) and the BPH. Although the responses of Qingliu to both insect pests appear vastly dissimilar, the phenylpropanoid pathway could be a convergent upstream pathway [65]. This study showed that the phenylpropanoid pathway is valuable for generating broad-spectrum resistance in rice cultivars.…”
Section: Discussionmentioning
confidence: 83%
“…OsBURP genes are known to play a role in plant vegetative and reproductive development and in tolerance to abiotic stresses (drought, salt stress, aluminum and cold) and respond to ABA 90 . In addition, OsBURP02 and OsBURP07 are induced 24 h after infestation by rice leafolder ( Cnaphalocrocis medinalis , Guenée, 1854, chewing insect) and brown planthopper ( Nilparvata lugens , Stahl, 1854, piercing-sucking insect) 33 . In rice, this induction of OsBURP might be prevented by the OS microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…During its evolutionary history, rice has developed several defense mechanisms against BPH, WBPH, and several other invaders [ 10 , 27 ]. Resistance to BPH is complex as it involves multiple sophisticated regulatory mechanisms both at the level of the insect and its host [ 28 ].…”
Section: Discussionmentioning
confidence: 99%